Parent engagement and therapeutic alliance in allied health teletherapy programs. (15th February 2021) - Fairweather, Glenn C.; Lincoln, Michelle; Ramsden, Robyn; Bulkeley, Kim
Abstract: Teletherapy services are being increasingly provided by allied health professionals to address major inequities of access. While clinical outcomes and stakeholder satisfaction are crucial for paediatric teletherapy's continued viability, processes for increasing parent/caregiver satisfaction, and for modifying aspects of caregiver engagement to improve outcomes, are under‐researched. Studies of in‐person therapy have shown that engagement, satisfaction and outcomes are influenced by the development of therapeutic alliance. This study investigates influences on parents' engagement with a teletherapy program and their therapeutic alliance with the therapist. Using a qualitative approach, data were analysed from semi‐structured telephone interviews with six parents in rural New South Wales, whose children had completed paediatric teletherapy programs provided by a psychologist, speech pathologist or occupational therapist. Parents described factors that affected aspects of their engagement and alliance. Thematic analysis with constant comparison was used to determine the themes of the interviews, which were (a) initial engagement, (b) collaboration and (c) rapport. The themes demonstrate that parents were evaluating the efforts the therapists were making in (a) communicating, (b) truly partnering with them, both being elements of collaboration and (c) building rapport with them and the child. A conceptual model, Parent And Caregiver Evaluation Cycle In Teletherapy (PACECIT), is proposed by the researchers to explain how parents evaluated the therapist to judge the current state of a personal relationship and to judge the effectiveness of a collaborative relationship, both influencing the therapeutic alliance and motivation for engagement. The findings emphasise the importance of fulfilling parent/caregiver expectations for clear and frequent communication, and discussion of their ideas. Also important is the development of therapeutic alliance through utilising parents' observations of non‐verbal communication to maintain an effective rapport and enhance engagement.